BENEFITS OF ARTIFICIAL INTELLIGENCE (CHATGPT) IN EDUCATION AND LEARNING: IS CHAT GPT HELPFUL? - Josephine Oranga (RADJA PUBLIKA, 2023)
The utilization of artificial intelligence in the education sector has increased gradually over the years. Further inventions in computing and supporting technology have resulted in the creation of robots and chatbots that improve students’ learning experiences from early childhood education all the way to higher education. Artificial intelligence in education, including the use of chatbots, has thus, been incorporated into instruction and administration. Accordingly, artificial intelligence (in the application of chatbot/robots (cobots) is routinely being utilized to teach typical tasks like pronunciation and spelling to children at lower levels of education. Notably, the interest to apply artificial intelligence in education is increasing by the day. Hence, this article delves into the benefits, challenges and disadvantages of utilization of artificial intelligence, and most notably, chatbots (ChatGPT) in education by getting responses from ChatGPT itself. Accordingly, the advantages of artificial intelligence in education include: provision of personalized learning, instant feedback and 24/7 availability amongst others. Hence, it is concluded that even though utilization of artificial intelligence (ChatGPT) can enhance learning, it should never replace human educators as chatbots work best when used in conjunction with human guidance and supervision, ensuring that learners receive a well-rounded and effective education.